1993
DOI: 10.1080/00102209308907612
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Curvature Effects on Laminar Premixed Flames: Stationary Cylindrical Flames

Abstract: A solution of the stationary cylindrical flame in both source and sink configurations is obtained analytically using simplified reaction rate and diffusion models. The solution is used to investigate the effects of curvature in the absence of stretch and identify the ranges where ducting and sourcelsink effects are dominant. We also investigate the concept of a minimum radius of curvature by introducing non-local effects on the flame.For both configurations a stable solution may be found for any imposed source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…These observations suggested that the flame penetration lengths were not strongly affected by the tube bends. This observation was in good agreement with the results of Echekki and Ferziger (1992) in their investigation into curvature effects on laminar premixed flames. They reported that curvature alone did not alter the flame propagation rate except for curvatures located near the source.…”
Section: Flame Length Data Reductionsupporting
confidence: 90%
“…These observations suggested that the flame penetration lengths were not strongly affected by the tube bends. This observation was in good agreement with the results of Echekki and Ferziger (1992) in their investigation into curvature effects on laminar premixed flames. They reported that curvature alone did not alter the flame propagation rate except for curvatures located near the source.…”
Section: Flame Length Data Reductionsupporting
confidence: 90%
“…The consumption speed of the flame at the centerline for the case of λ fh = 0 is higher compared to the laminar burning velocity of a corresponding planar flame. It is known that a negative curvature (flame concave towards the reactants) acts to increase the flame burning velocity [36,37], when the radius of curvature of the flame is comparable with the flame thickness. The values of S c,0 are slightly lower when heat exchange is allowed compared to the case with λ fh = 0, primarily because the flame becomes weaker as discussed before.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that these solutions involving the confluent hypergeometric functions apply to a more general family of problems, that is, planar and axisymmetric edge flames in counterflow. Also note that these solutions resemble those describing stationary cylindrical premixed flames, Echekki & Ferziger (1993), and also involve confluent hypergeometric functions. Important properties of Kummer's functions M and U are dM…”
Section: Appendix the Stationary Solutionsmentioning
confidence: 66%